Shadow on the mountain : Nancy Pfister, Dr. William Styler, and the murder of Aspen's golden girl - Singular, Stephen; Singular, Joyce (St. Martin's Press, 2016)
"Nancy Pfister, heir to Buttermilk Mountain, the world-renowned site of the Winter X Games, was Aspen royalty, its ambassador to the world. She lived among the rich and famous...But behind the warm facade, she could be selfish, manipulative, and careless. Pfister enjoyed bragging about her wealth and celebrity connections, but those closest to her, like Kathy Carpenter, Pfister's personal assistant, drinking companion, and on one occasion lover, knew better. In 2013, after a long fall from grace, Dr. William Styler and his wife, Nancy, relocated to Aspen to reinvent themselves...and Nancy Pfister was their answered prayer. She took them in, gave them a place to live, and allowed them to launch their new spa business... When Nancy was found beaten to death in her own home, the Stylers and Carpenter were all under suspicion for the gruesome murder."--